Church subsidy and Philip v’s politics in the Indian Church: a path to explore (Tzintzun, Revista de Estudios Históricos, 2016)
he main goal of the present paper is to demonstrate that the study of churchsubsidies constitute a viable investigation line and path in order to ind outmore about church policies and the New Hispanic Church in Philip v’s era,a period that has been little studied. In that regard, it needs to be pointedout that in the historiography of the modern era of Spain, Philip v’s reign isgenerally labelled as a “projectist” period, meaning that it welcomed the irstattempts to carry out reforms. hese reformist tendencies need to be linkedwith the events of the so-called Western Indies in the same period, as seriousattempts to change church policies can be observed here. In this sense, thestudy of the introduction of church subsidies, as well as its consequences inthe New Hispanic church and clergy, can be a feasible path as it closely showsthe formulation of the irst reform plans of the Bourbons towards the IndianChurch in the irst decades of the 18th century.
Keywords: Philip v; church subsidy; Archbishopric of Mexico; documentary sources; 18th century